Free-standing large, ultrathin germanium selenide van der Waals ribbons by combined vapor–liquid–solid growth and edge attachment. Issue 16 (8th April 2022) - Sutter, Eli; French, Jacob S.; Sutter, Peter
Abstract : High-yield synthesis of large, ultrathin GeSe ribbons combining longitudinal vapor–liquid–solid growth with lateral edge incorporation. Intense luminescence confirms high quality GeSe with low concentration of nonradiative recombination centers. Abstract : Among group IV monochalcogenides, layered GeSe is of interest for its anisotropic properties, 1.3 eV direct band gap, ferroelectricity, high mobility, and excellent environmental stability. Electronic, optoelectronic and photovoltaic applications depend on the development of synthesis approaches that yield large quantities of crystalline flakes with controllable size and thickness. Here, we demonstrate the growth of single-crystalline GeSe nanoribbons by a vapor–liquid–solid process over Au catalyst on different substrates at low thermal budget. The nanoribbons crystallize in a layered structure, with ribbon axis along the armchair direction of the van der Waals layers. The ribbon morphology is determined by catalyst driven fast longitudinal growth accompanied by lateral expansion via edge-specific incorporation into the basal planes. This combined growth mechanism enables temperature controlled realization of ribbons with typical widths of up to 30 μm and lengths exceeding 100 μm, while maintaining sub-50 nm thickness. Nanoscale cathodoluminescence spectroscopy on individual GeSe nanoribbons demonstrates intense temperature-dependent band-edge emission up to room temperature, with fundamental bandgap and temperature coefficient of E g (0) = 1.29 eV and α = 3.0 × 10 −4 eV K −1, respectively, confirming high quality GeSe with low concentration of non-radiative recombination centers promising for optoelectronic applications including light emitters, photodetectors, and solar cells.